Good education policy making: Data-informed but values-driven. (December 2018) - Brighouse, Harry; Ladd, Helen; Loeb, Susanna; Swift, Adam
In this article, based on their book Educational Goods: Values, Evidence and Decision Making, Harry Brighouse, Helen Ladd, Susanna Loeb, and Adam Swift encourage education decision makers to give careful thought to the values that underlie the data they collect and use to inform policy. Rather than basing decisions entirely on what improves academic achievement, the authors call for attention to a wider array of values, which they call educational goods. These include the capacities to function in the labor market, to participate effectively in the democratic process, to make autonomous judgments about key life decisions such as occupation or religion, to develop healthy interpersonal relationships, to seek personal fulfilment, and to treat others with respect and dignity. Thinking in terms of these values can broaden the conversation about education priorities and bring clarity to decisions involving trade-offs and conflicting aims .